Importance of cost engineering in the budget of a civil construction project (Research, Society and Development, 2022)
The objective was to evaluate the importance of elaborating a cost plan within civil construction in order to avoid future losses in the works and maximize the profit of the clients. Thus, an assessment of the costs that most burden civil construction projects was carried out to get to the root of the problem. Any failure in the execution of a project can lead to expenses that were not foreseen, hence the importance of efficient planning. The methodology was based on a systematic review. The results indicate that it is necessary to know the concept and applicability of costs, understanding that there are several indispensable items in a work that must be taken into account, especially the price of materials and qualified labor, always aiming at financial viability and service quality. offered, bringing profit to builders and showing that a project of excellence can be made that meets the needs of customers. Through the available resources, it is possible to project with greater precision the completion of the work, as it is challenging to deliver a project compatible with the initial idea, due to the additives present in the works. Thus, due to the high price of inputs, it is extremely important to adopt measures that promote budget reduction for civil construction, such as financial planning regarding fixed and variable costs, in addition to the constant evaluation of suppliers, always seeking the right balance between expenses, quality of service offered and time.